Effects of the combination of the gratitude extension-construction theory and peer interactive education on self-management ability and quality of life in school-age children with asthma in China - Gao, Lijin; Liu, Lijia; Zhang, Wen; Chen, Haixin; Wei, Xiuming; Guo, Yawei; Zhou, Xiaohua; Zheng, Yibo (Frontiers in Pediatrics, 2025)
ObjectiveTo explore the effects of the combination of the gratitude extension-construction theory and peer interactive education on self-management ability and quality of life in school-age children with asthma in China.MethodsA total of 120 children with bronchial asthma admitted to Bethune International Peace Hospital, Shijiazhuang, China from January 2023 to March 2024 were selected and randomly divided into study group and control group. The control group accepted routine treatment and nursing. Based on routine treatment and nursing, the study group accepted the combination of the gratitude extension-construction theory and peer interactive education. The self-management ability, asthma control score, lung function, quality of life, recurrence, nursing compliance and nursing satisfaction were compared in both groups.ResultsCompared to before intervention, the self-management ability scores, C-ACT score, levels of lung function indexes and PAQLQ scores were elevated at 6 and 12 months after intervention (P < 0.05). Compared to the control group, the study group had higher self-management ability scores, C-ACT score, levels of lung function indexes and PAQLQ scores at 6 and 12 months after intervention (P < 0.05). Compared to the control group, the study group had lower frequency of asthma attacks, emergency department and hospitalization within 12 months after treatment, better nursing compliance and higher nursing satisfaction (P < 0.05).ConclusionThe combination of the gratitude extension-construction theory and peer interactive education significantly promote the self-management ability, improve lung function, promote the quality of life, reduce the recurrence, and enhance the nursing compliance and nursing satisfaction of school-age children with asthma in China.